Bathtub Dramaturgy: An Experimental Syllabus for Theatre and Performance Studies Classrooms - Edmonson, Chloë Rae (Performance Matters, 2023)
This annotated syllabus proposes an undergraduate course designed to develop dramaturgical methods around a common theme. While the course focuses on performances in and around bathtubs, the ultimate goal of this essay is to put forward methods that can be applied across an expansive range of theatre and performance studies topics. Each unit in the proposed course explores a different facet of dramaturgical practice with corresponding assignments that challenge students to practise essential research, writing, and communication skills. These assignments culminate in a final project: the presentation of students’ own devised bathtub performances. This syllabus, aiming toward a restorative pedagogy, imagines a future in-person classroom where students can collectively explore the relationship between public and private through bathtubs as a microcosm for the complexity of human experience.